2015
DOI: 10.14503/thij-14-4612
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Organism Infections in Patients with Left Ventricular Assist Devices

Abstract: H eart failure is a chronic disease state with substantial morbidity and mortality rates.1 End-stage heart failure is characterized by worsening symptoms despite optimal medical management, and heart transplantation is the definitive treatment. However, rates of heart failure are increasing, whereas the number of organs available for transplantation is static.2 Therefore, mechanical support for the failing heart, especially ventricular assist devices (VADs), has attracted strong interest. Left VAD (LVAD) impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…30 However, two other studies did not find infection to be associated with increased mortality, although they did show increased hospital length of stay in patients with infection. 23,31 LVAD infections were reported as a leading cause for readmission in 5 studies. 17,3235…”
Section: Resultsmentioning
confidence: 99%
“…30 However, two other studies did not find infection to be associated with increased mortality, although they did show increased hospital length of stay in patients with infection. 23,31 LVAD infections were reported as a leading cause for readmission in 5 studies. 17,3235…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is only one study reviewing such issue. Donahey et al 27 Besides, to our knowledge, there is no study assessing the potential relapse of BHED associated infection after HT. All three infections that relapsed were either VAD-S or VAD-R. Of note, relapsing infections occurred between 3 and 11 days after removal of the device and HT, which might suggest that an infection specific or related to the BHED, could be a harbinger of a future infection by the same microorganism few days after HT (especially if it is in close distance to the device).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only one study reviewing such issue. Donahey et al . described a colonization rate of 31.6% with no significant differences in mortality or device explantation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be multifactorial in the setting of sepsis and also underlying comorbidities that would increase the mortality by itself. There were a few studies that showed no significant long-term outcomes in people with these infectious complications, although they showed increased length of hospital stay [12,[18][19]. A few studies have shown that LVAD infections have significant association with poor survival after adjusting for age and co-morbidities [20].…”
Section: Discussionmentioning
confidence: 99%